Design and Construction of Lightweight Steel Roof Structure for Kaleles Sapi Kerapan Sumenep - Ishaq; Firatama, Aditya Dandy; Triono, Ipung Wisnu; Ifan, Mohammad (Yayasan Ghalih Pelopor Pendidikan (Ghalih Foundation), 2026)
The need for efficient and environmentally friendly building construction demands innovation in material selection and structural design, including the use of lightweight steel roofs. This study aims to design a lightweight steel roof structure adopting the Kaleles Sapi Kerapan design in Sumenep that safely withstands loads, efficiently uses materials, and supports solar panel integration as an alternative energy source. The methodology includes literature study, geometry and material data collection, and numerical modeling using SAP2000 v22.0.0 Ultimate software with linear static analysis according to SNI 7971:2013. Loads analyzed include dead load, live load, and wind load with various combinations. Simulation results indicate the roof frame design has strength ratios below 1 and is therefore safe. The total material requirements include C75 trusses, battens, braces, screws, spandek sheets, and ridge elements in measured quantities. This lightweight steel roof design is structurally feasible, economical, and supports sustainable building concepts.